2002
DOI: 10.17221/3520-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ozone on properties of jams

Abstract: The influence of ozone on some properties of fruit jams was studied. Ozone did not influence the pH value, the contents of reducing sugars and organic acids, or the sensoric properties of the fruit jams tested. It may be used as a source of sterile air over the jam surfaces in yoghurt production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…In similar studies, Polívka et al [21], Soja et al [22], and Silva et al [7] did not observe the effect of juice ozonation in relation to the content of reducing sugars (RS). Polívka et al [21] found only a non-significant variation of 10.0% in RS.…”
Section: Discussionmentioning
confidence: 90%
“…In similar studies, Polívka et al [21], Soja et al [22], and Silva et al [7] did not observe the effect of juice ozonation in relation to the content of reducing sugars (RS). Polívka et al [21] found only a non-significant variation of 10.0% in RS.…”
Section: Discussionmentioning
confidence: 90%